Effect of UPNV Jatim Pocity to be a PTN on Perfomance and Lecturer Revenues - Niniek Imaningsih; Sishadiyati (Nusantara Science and Technology Proceedings)
Subjective well-being is a person's perception of his life experience consisting of cognitive and effective evaluation of life and represents it in his psychological well-being. Subjective welfare perceived by a lecturer can be said to have a direct effect on job satisfaction. Job satisfaction is closely related to employee attitudes to various factors in the work, among others: work situation, social influence in work, rewards, and other factors. Job satisfaction is the general attitude of an individual to his work. For this reason, it is necessary to examine the work satisfaction of lecturers from the subjective well-being through income (Salary and Lecture Certificate allowances) obtained and also the emotional intelligence (lecturer Intelligence) aspect. Subjective intelligence of UPN “Veteran” of East Java lecturers either civil servants or PTY there is a difference in meanings changed as various allowances still exist, and paid even though Lecture Certificate allowances are paid at the end of the month and instead receive full (100% before PTN is paid 50%). Emotional intelligence of UPNV lecturers in East Java there is a change even increased because of related BKD (Load Activity lecturer) if not doing the three activities then do not get the functional allowance or allowance Lecture Certificate.